TTBK1 and CK1 inhibitors restore TDP-43 pathology and avoid disease propagation in lymphoblast from Alzheimer’s disease patients - Martinez-Gonzalez, Loreto; Cuevas, Eva P.; Tosat-Bitrián, Carlota; Nozal, Vanesa; Gil, Carmen; Palomo, Valle; Martín-Requero, Ángeles; Martinez, Ana (Frontiers in Molecular Neuroscience, 2023)
Introduction TDP-43 proteinopathy in Alzheimer’s disease (AD) patients is recently emerging as a relevant pathomolecular event that may have been overlooked. Recent results in immortalized lymphocytes from AD patients have shown not only an increase of post-translational modifications in TDP-43, such as hyperphosphorylation and fragmentation, but also its prionic behaviour and cell-to-cell disease transmission. With the main goal to advance therapeutic interventions, we present in this work different kinase inhibitors with potential to restore this pathological mechanism. Methodology We have used immortalized lymphocytes from healthy controls and AD severe patients to evaluate the correction of TDP-43 pathology after the treatment with previously synthetized TTBK1 and CK1 inhibitors. Moreover we used the conditioned mediums of these cells to perform different disease propagation experiments. Results TDP-43 pathology observed in lymphoblasts from severe AD patients is reduced after the treatment with TTBK1 and CK1 inhibitors (decreasing phosphorylation and increasing nuclear localisation), Furthermore, the significant increase in TDP-43 phosphorylation, cytoplasmic accumulation and aberrant F-actin protrusions (TNT-like structures) observed in control cells growing in CM from AD lymphoblasts were abolished when the CM from AD lymphoblasts treated with previously reported TTBK1 and CK1 inhibitors were used. In addition, the cytosolic transport mediated by molecular motors of the receptor cells was altered with the induced TDP-43 pathology, but it was not produced with the abovementioned pretreated CMs. Conclusion TTBK1 and CK1 inhibitors, specially VNG1.47 and IGS2.7 compounds, restore TDP-43 pathology and avoid cell-to-cell propagation in immortalized lymphocytes from AD patients, being excellent candidates for the future therapy of this prevalent and devastating disease.